"Elements of resistance in the Palestinian poetry "Free Verse - Mulla Ibrahimi, Ezzat; Jandallah, Hamid; Azadi, Azada (Journal of Humanities & Social Sciences, 2017)
Palestinian contemporary poetry is actually the voice of a nation who tries to reveal its positions against the enemy via poems. The poet is the describer of poverty, oppression, tyranny, subjugation and terror calling for resistance and fighting against the occupiers. Longing for going back to his homeland, he writes of his love for the country. Calling everyone to rise for a revolution, the poet is proud of his glorious Arab history while being outraged by his lost identity. In this analytical-descriptive study, it was tried to extract the main elements of resistance in the “modern” Palestinian poetry. The findings of the study show that the “modern” poetry abounds with concepts such as calling for resistance, extoling the distinguished positions of martyrs and praising the freedom fighters of the world. Utilizing different techniques such as, symbolic language, mythology, masking and calling, al-Manasra is one of the Palestinian poets who have tried to express his empathy with the Palestinian resistance movement.